MMDA EDSA REVOLUTION : A PR CAMPAIGN ( March 2007 ) - Cruz, Jinky R.; Poblacion, Rosario A.; Ramirez, Glaiza U. and Ronquillo, Paola M. 4 0 16; 5 (2007)
u
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila, 2007.;Bachelor of Science in Mass Communication.
Keywords: 2 -- 0; 6; 20; 20; 2